Identification of RNAi hypoallergic bread wheat lines for wheat-dependent exercise-induced anaphylaxis patients - Guzmán-López, María H.; Ruipérez, Violeta; Marín-Sanz, Miriam; Ojeda-Fernández, Isabel; Ojeda-Fernández, Pedro; Garrote-Adrados, José Antonio; Arranz-Sanz, Eduardo; Barro, Francisco (Frontiers in Nutrition, 2024)
Wheat-dependent exercise-induced anaphylaxis (WDEIA) is one of the most severe forms of wheat allergy. It occurs in patients when they exercise after ingesting wheat-containing foods. Nowadays, the only possible alternative for WDEIA patients is to avoid such foods. This study investigated the potential of six RNA of interference (RNAi) wheat lines with low-prolamin content as alternatives for WDEIA patients. For that purpose, a high performance-liquid chromatography (HPLC) analysis was performed to evaluate differences in gluten protein fractions among these lines. Next, western blots were conducted to measure the immunoglobulin E (IgE) reactivity to wheat proteins in sera from five WDEIA patients. Additionally, monoclonal antibodies (moAb) recognition sites and the IgE binding sites were searched in all peptides identified by LC-MS/MS after protein digestion. The results showed a 61.4 -81.2% reduction in the gliadin content of the RNAi lines, accompanied by an increase in their high-molecular weight (HMW) glutenin content compared to the wild type bread wheat line (WT). In all cases, the reduction in gliadin content correlated with a decrease in IgE reactivity observed in the sera of WDEIA patients, highlighting the E82 and H320 lines. These two RNAi lines exhibited a ≤90% reduction in IgE reactivity. This reduction could be attributed to an absence of IgE binding sites associated with α-and ω5-gliadins, which were present in the WT. Overall, these lines offer a potential alternative for foodstuff for individuals with WDEIA.